Isolation and Characterization of a Putrefactive Anaerobe Clostridium sporogenes from Fishes and Shell Fishes - K.V., Lalitha; K., Mahadeva Iyer (Fishery Technology, 2025)
Fishes and shell fishes were analysed for the occurrence of Clostridium sporogenes. 21 isolates of C. sporogenes were examined for cultural properties and heat resistance. All the strains isolated were found to be poor sporeformers. The spores of the above C. sporogenes strains were highly heat resistant.